Four Lessons Learned from Complications in Head and Neck Microvascular Reconstructions and Prevention Strategies. Issue 1 (January 2021) - Vieira, Luís; Isacson, Daniel; Dimovska, Eleonora O. F.; Rodriguez-Lorenzo, Andres
Abstract : Background: Free flap reconstruction in the head and neck region is a complex field in which patient comorbidities, radiation therapy, tumor recurrence, and variability of clinical scenarios make some cases particularly challenging and prone to devastating complications. Despite low free flap failure rates, the impact of flap failure has enormous consequences for the patients. Methods: Acknowledging and predicting high risk intra- and postoperative situations and having planned strategies on how to deal with them can decrease their rate and improve the patient's reconstructive journey. Results: Herein, the authors present 4 examples of significant complications in complex microvascular head and neck cancer reconstruction, encountered for the last 10 years: compression and kinking of the vascular pedicle, lack of planning of external skin coverage in osteoradionecrosis, management of the vessel-depleted neck, and vascular donor site morbidity after fibula harvest. Conclusion: The authors reflect on the causes and propose preventative strategies in each peri-operative stage.